2019
DOI: 10.1074/jbc.ra119.008592
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and structural differences between heme oxygenase-1 and -2 are due to differences in their C-terminal regions

Abstract: Heme oxygenase (HO) catalyzes heme degradation, a process crucial for regulating cellular levels of this vital, but cytotoxic, cofactor. Two HO isoforms, HO1 and HO2, exhibit similar catalytic mechanisms and efficiencies. They also share catalytic core structures, including the heme-binding site. Outside their catalytic cores are two regions unique to HO2: a 20-amino acid–long N-terminal extension and a C-terminal domain containing two heme regulatory motifs (HRMs) that bind heme independently of the core. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…Because we compared the H45W/G159W variant to itself (not to wild-type protein), changes in exchange were strictly due to the presence of heme, not the mutations themselves. Further, the changes observed with the H45W/G159W variant are quite distinct from those of previous observations in which heme was in the core (20). In those experiments, no difference in uptake was observed between wild-type Fe 3+ core/HRM-HO2sol R relative to wild-type Fe 3+…”
Section: Downloaded Fromcontrasting
confidence: 75%
See 2 more Smart Citations
“…Because we compared the H45W/G159W variant to itself (not to wild-type protein), changes in exchange were strictly due to the presence of heme, not the mutations themselves. Further, the changes observed with the H45W/G159W variant are quite distinct from those of previous observations in which heme was in the core (20). In those experiments, no difference in uptake was observed between wild-type Fe 3+ core/HRM-HO2sol R relative to wild-type Fe 3+…”
Section: Downloaded Fromcontrasting
confidence: 75%
“…Lastly, a significant level of protection in the area around residue 100 was observed in the H45W/G159W variant. We have previously noted protection from exchange in this region upon heme binding to the core of HO2, when protection is also observed in the distal helix (20), suggesting that the two regions interact in some way. Thus, overall, the H45W/G159W variant appears to have a similar global structure as wild-type HO2sol, with the substitutions having introduced some rigidity into the heme binding pocket.…”
Section: Hrm-ho2mentioning
confidence: 74%
See 1 more Smart Citation
“…In HO2, one KFERQ-like motif, 52[QFVKD]57, absent in HO1, is found at the proximal helix, which harbors the heme ligand His45 at the HO2 catalytic site. According to our HDX-MS analysis, compared with an apo-active site, decreased deuterium incorporation at the proximal helix was observed when heme is bound at the catalytic site (45). This heme-dependent protection of the KFERQ-like motif could explain how the apo active site of HO2 is differentially recognized by the lysosomal degradation machinery, leading to more rapid protein degradation.…”
Section: Discussionmentioning
confidence: 71%
“…This finding clearly shows that the degradation signal is not triggered by changes in the levels of the products (CO, Fe, biliverdin) of heme degradation. Our recent hydrogen-deuterium exchange mass spectrometry (HDX-MS) studies demonstrated that in H45W/G159W variant, the tryptophan mutations themselves led to minimal to no structural perturbations and that the only observed differences in HDX-MS related to heme binding to the catalytic core were specific to the distal and proximal helices, which form the heme binding pocket (45). Furthermore, the circular dichroism spectra of wild-type HO2 and the H45W/G159W variant were nearly indistinguishable (30).…”
Section: Discussionmentioning
confidence: 99%